Causal Analysis of Policy Effects on Fertility - Rannveig Kaldager Hart; Janna Bergsvik; Agnes Fauske; Wookun Kim (Center for Economic Studies and ifo Institute (CESifo), 2023)
This chapter reviews the literature on the causal effects of policies on fertility. It focuses on evidence from experiments and quasi-experiments in low fertility contexts, including studies from Europe, Northern America, Oceania and Asia. Making no a priori restrictions on policy type, the review encompasses evaluations of parental leave, childcare, health insurance, and financial incentives such as child transfers. Childcare expansions increase completed fertility. Financial incentives had positive effects on fertility across contexts, both in the short and long run. Expansions of parental leave rights in Central Europe, and introduction of parental leave in the U.S., also had positive effects. Distributional effects of these policies are very different, with parental leave compensation benefiting high-earning couples, while expansions of child care programs have potential to reduce social inequalities.
Keywords: J13; J18; H53; I18; 330; fertility; parental leave; cash transfers; childcare; healthcare; public policy; causal effect